PENGGUNAAN ALAT PERAGA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Ignasius Igo Seran (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The PJOK subject in its implementation must be pursued with the conditions of learning that are conducive in the sense of an active, creative, effective and even innovative learning. To create conducive learning conditions, it is necessary to make an effort to maximize the use of existing facilities and infrastructure, even if it is deemed necessary for a teacher to make the necessary teaching aids themselves. PJOK lesson material can not only be conveyed through information or only rely on theories, but must be sought for evidence in an effort to avoid verbalism. It's just that the reality that occurs in the field is that most of the use of teaching aids in PJOK learning, both direct and imitation / artificial, has not been sufficiently optimized in elementary schools in general. This reality is also experienced in class VI SDK I Kiwangona East Adonara District East Flores Regency 2017/2018 Academic Year where the classroom action research is conducted. From the results of observations conducted by researchers on the school used as a place of research, when the learning process the teacher only explains the subject matter with theories without the help of the right teaching aids. As a result student learning outcomes are lacking, lack of understanding the theory being studied and student activities are not visible, because the learning process is teacher-centered. Based on the background above, in general the problems in this study are: "Can the use of Teaching Devices improve the understanding of PJOK for class VI students of SDK I Kiwangona, East Adonara District, East Flores District. Academic Year 2017/2018